Pneumococcal vaccine uptake and vaccine effectiveness in older adults with invasive pneumococcal disease in Germany: A retrospective cohort study - Stephanie Perniciaro; Mark van der Linden (Elsevier, 2021)
Background: Invasive pneumococcal disease (IPD) in people ≥60 years old is on the rise in Germany. There has been a recommendation for pneumococcal vaccination in this age group since 1998. Methods: We determined the vaccination status of people ≥60 years old with IPD in Germany. We assessed vaccine effectiveness (VE) of the recommended 23-valent polysaccharide vaccine (PPV23) against IPD using the indirect cohort method. Results: The rate of pneumococcal vaccination in older adults with IPD is low, 26%, with only 16% of people receiving a pneumococcal vaccine within five years of the IPD episode. Age- and gender- adjusted vaccine effectiveness (VE) for PPV23 was 37% (95% confidence interval 12% - 55%). For people vaccinated with PPV23 less than two years prior to IPD, VE was -20% (-131% - 34%), between two and four years prior to IPD, VE was 56% (20% - 76%), and 47% (17% - 63%) for those vaccinated ≥5 five years ago. Excluding serotype 3, overall VE for the remaining serotypes in PPV23 was 63% (49% - 74%). For people receiving PPV23 within the past two years, VE against all serotypes except 3 was 49% (12% - 71%); for people vaccinated between two and four years prior to IPD 66% (37% - 82%); for those vaccinated ≥five years ago, 69% (50% - 81%). VE of PPV23 against serotype 3 IPD only was -110% (-198% - -47%). Conclusions: To reduce IPD in older adults in Germany, we must increase the rate of pneumococcal vaccine uptake. For 22/23 serotypes, PPV23 was effective. Serotype 3 remains a major problem.